LOCAL AREA NETWORK MANAGEMENT (Case Study at Assessment and Development Information Technology Units Brawijaya University Malang) - Mohammad Firman Hadiwijaya (Fakultas Ilmu Administrasi Universitas Brawijaya, 2015)
The purpose of this study was to know the management local area network at Assessment and Development Information Technology units, furthermore this study focusing on network management functions that applied by Assessment and Development Information Technology Units. This study will explain about the implementation of network management functions in the local area network management. The research method employ in this research is by using descriptive qualitative method by study case approach. The results of this study was in the implementation of network management functions Assessment and Development Information Technology units already applied all five network management functions in the local area network management. Each functions represented as a network management components in managing Assessment and Development Information Technology units local area network. Since the network management functions represented as a network management components it needed improvement in each network management functions policies and measurements. Keywords: Local Area Network Management